TRANSFORMASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM MELALUI ISLAMIC DIGITAL LEARNING BERLANDASKAN PRINSIP TA’LIM DI SMP NEGERI 2 PALENGAAN PAMEKASAN - Riski, Ulfatur; Imamuddin, M.; Jannah, Islamiatul; Sayyi, Ach. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the transformation of Islamic Religious Education through Islamic Digital Learning grounded in the principle of ta’lim at SMP Negeri 2 Palengaan, Pamekasan. The study employed a qualitative approach with a single-case study design. The participants consisted of the principal, vice principal for curriculum, two Islamic Religious Education teachers, a guidance and counseling teacher, and five students selected purposively. Data were collected through semi-structured interviews, observations, and document analysis, and were subsequently analyzed thematically through coding, categorization, theme development, and interpretation. The findings indicate that the transformation of Islamic Religious Education was carried out through the use of videos, digital presentations, online resources, electronic quizzes, and reflective activities that expanded learning access, increased instructional variation, and encouraged student participation. The principle of ta’lim was actualized through the curation of religious sources, systematic delivery of knowledge, reinforcement of the teacher’s role as an epistemic guide, and development of students’ digital responsibility. Its implementation was supported by school policies, teacher readiness, facilities, and student enthusiasm, but remained constrained by limited internet connectivity, devices, digital competence, and operational guidelines. The study confirms that digital transformation in Islamic Religious Education must sustainably integrate technology, pedagogy, knowledge validity, and digital ethics.